Cocker Spaniel - Fogle, Bruce; Morgan (London Dorling Kindersley, 1996)
Essential Informationon day - To - Day Care, breeding and showing, discover the history , physical traits and temperament of the cockerand american cocker spaniel
included index
11
Keywords: Breeding; Dogs